2021
DOI: 10.1186/s12933-021-01324-4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of hematological parameters for micro- and macrovascular outcomes in patients with type 2 diabetes: the Rio de Janeiro type 2 diabetes cohort study

Abstract: Background The prognostic importance of several hematological parameters has been scarcely investigated in type 2 diabetes. So, we aimed to evaluate their prognostic importance for development of complications in a cohort of type 2 diabetes. Methods In a prospective study, 689 individuals with type 2 diabetes had blood red cell, platelet and leukocyte parameters obtained at baseline. Multivariate Cox analyses examined the associations between sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…A Turkish study also reported that the highest MHR was related to a 1.8-fold and 1.5-fold risk of in-hospital and long-term cardiovascular mortality, respectively [ 28 ]. Additionally, this relationship was confirmed in patients diagnosed with renal insufficiency [ 18 , 30 ] and type 2 diabetes [ 19 ]. However, cardiovascular mortality did not differ between the low-MHR and high-MHR groups in a study of patients commencing dialysis [ 31 ].…”
Section: Discussionmentioning
confidence: 89%
“…A Turkish study also reported that the highest MHR was related to a 1.8-fold and 1.5-fold risk of in-hospital and long-term cardiovascular mortality, respectively [ 28 ]. Additionally, this relationship was confirmed in patients diagnosed with renal insufficiency [ 18 , 30 ] and type 2 diabetes [ 19 ]. However, cardiovascular mortality did not differ between the low-MHR and high-MHR groups in a study of patients commencing dialysis [ 31 ].…”
Section: Discussionmentioning
confidence: 89%
“…Hypoalbuminemia was associated with mortality in patients regardless of the implicated disease, even in a healthy population ( 25 ). Lymphocytes reflected the immune regulatory response ( 26 ). Lymphocyte count and leukocyte ratios that mainly included lymphocyte were predictors of mortality in patients with type 2 diabetes and DFUs ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes reflected the immune regulatory response ( 26 ). Lymphocyte count and leukocyte ratios that mainly included lymphocyte were predictors of mortality in patients with type 2 diabetes and DFUs ( 26 , 27 ). Lower BMI was found to be associated with mortality in patients with diabetes and DFUs in recent studies ( 28 , 29 ), which was consistent with our finding: BMI was negatively associated with all-cause mortality in the unadjusted Cox regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated whether LSM, CAP or both were able to improve risk discrimination in relation to a basic standard risk factor model. For addressing it, we performed analyses using two metrics of model risk discrimination improvement: the increase in C-statistics (i.e., the area under curve applied to time-to-event Cox analysis) and the relative Integrated Discrimination Improvement (IDI) index, which measures the percentage increase in the discrimination slope after including the TE parameters in relation to that of the basic model [ 25 , 26 , 28 ]. In all analyses a two-tailed probability value < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%